Impoliteness Strategies In Joe Biden’s Instagram Comment Section - Siti Patimah; Desy Rusmawaty; Yuni Utami Asih (English Department, Faculty of Teacher Training and Education, Mulawarman University, 2022)
This study investigates linguistic impoliteness found in Joe Biden’s Instagram comment section through the analysis of impoliteness strategies proposed by Jonathan Culpeper. The present study aims at examining the types of impoliteness strategies used by commenters in Joe Biden Instagram comment section. The study uses descriptive qualitative method. The data gathered by using documentary technique, in which only the data that support research question are taken. Findings showed that there are four out five types of impoliteness strategies that used by commenters in Joe Biden’s Instagram comment section. Furthermore, there were some functions of impoliteness that the researcher found; coercive impoliteness, affective impoliteness, and entertaining impoliteness. The result showed that the commenter demonstrated the expression of wrath and dissapointment. The advantages of using online communication and ability to exercise their power eventhough they were in a lower social status also contributed to the emergence of impolite act. But, the lack of feedback from the target regarding the impolite comment on his Instagram post make this study less detailed. In short, it is recommended to investigate more comprehensively the impoliteness strategies in a case where the target showed clear response toward the impoliteness act